A5.4 Anti Carbamylated Protein Antibodies (Anti-CarP) Are Present in Arthralgia Patients and Predict the Development of Rheumatoid Arthritis. (25th February 2013) - Shi, Jing; Stadt, Lotte A van de; Levarht, EW Nivine; Huizinga, Tom WJ; Toes, René EM; Trouw, Leendert A; Schaardenburg, Dirkjan van
Abstract : Background/Objective: Recently, we discovered a new auto- antibody system in rheumatoid arthritis (RA): anti carbamylated protein antibodies (anti-CarP). These antibodies have additional prognostic value in predicting joint destruction when compared to anti-citrullinated protein antibodies (ACPA). However, it is not yet known whether anti-CarP antibodies are present before the diagnosis of RA and whether they have predictive value for the development of RA. Therefore we studied whether anti-CarP antibodies are present in arthralgia patients and whether their presence associates with the development of RA. Methods: Sera of 340 arthralgia patients without clinical signs of arthritis and 32 healthy controls were measured for the presence of anti-CarP IgG antibodies. One hundred eleven arthralgia patients (33%) were IgM-rheumatoid factor (IgM-RF) positive/anti-cyclic citrullinated peptide 2 (aCCP2) negative and 229 (67%) were aCCP2 positive. Patients were followed for the development of RA (2010 criteria). The median follow up time was 36 months. Cox regression analysis was performed to compare the risk of developing RA between Anti-CarP positive and negative arthralgia patients in follow up time. Results: The arthralgia cohort consisted of 340 IgM-RF and/or aCCP positive patients. Anti-CarP antibodies were present in sera of 113 (39%) of the tested patients. A total of 120 patients developed RA after a median (IQR) of 12 (6–24) months. The presence of anti-CarP antibodies was associated with the development of RA in the whole arthralgia cohort even after correction for RF and aCCP2 status (HR: 1.56; 95%CI: 1.06–2.29; p = 0.023), as well as in the aCCP2 positive subgroup (OR: 2.231; 95%CI: 1.31–3.79; p = 0.003). Conclusions: Anti-CarP antibodies were present in arthralgia patients and their presence predicted the development of RA independent of aCCP2 antibodies. Disclosure: These studies were financially supported by Janssen Biologics BV, (Johnson & Johnson).